Spatio‐temporal heterogeneity in river sounds: Disentangling micro‐ and macro‐variation in a chain of waterholes. (11th December 2019) - Karaconstantis, Chris; Desjonquères, Camille; Gifford, Toby; Linke, Simon
Abstract: Passive acoustic monitoring is gaining momentum as a viable alternative method to surveying freshwater ecosystems. As part of an emerging field, the spatio‐temporal replication levels of these sampling methods need to be standardised. However, in shallow waters, acoustic spatio‐temporal patchiness remains virtually unexplored. In this paper, we specifically investigate the spatial heterogeneity in underwater sounds observed within and between waterholes of an ephemeral river at different times of the day and how it could affect sampling in passive acoustic monitoring. We recorded in the Einasleigh River, Queensland in August 2016, using a linear transect of hydrophones mounted on frames. We recorded four times a day: at dawn, midday, dusk, and midnight. To measure different temporal and spectral attributes of the recorded sound, we investigated the mean frequency spectrum and computed acoustic indices. Both mean frequency spectrum and index analyses revealed that the site and diel activity patterns significantly influenced the sounds recorded, even for adjacent sites with similar characteristics along a single river. We found that most of the variation was due to temporal patterns, followed by between‐site differences, while within‐site differences had limited influence. This study demonstrates high spatio‐temporal acoustic variability in freshwater environments, linked to different species or species groups. Decisions about sampling design are vital to obtain adequate representation. This study thus emphasises the need to tailor spatio‐temporal settings of a sampling design to the aim of the study, the species and the habitat.